Non-histone lactylation: unveiling its functional significance - Pusong Shi; Yongjie Ma; Yongjie Ma; Yongjie Ma; Yongjie Ma; Yongjie Ma; Shaolu Zhang; Shaolu Zhang; Shaolu Zhang; Shaolu Zhang; Shaolu Zhang (Frontiers in Cell and Developmental Biology)
Lactylation, a newly discovered protein posttranslational modification (PTM) in 2019, primarily occurs on lysine residues. Lactylation of histones was initially identified, and subsequent studies have increasingly demonstrated its widespread presence on non-histone proteins. Recently, high-throughput proteomics studies have identified a large number of lactylated proteins and sites, revealing their global regulatory role in disease development. Notably, this modification is catalyzed by lactyltransferase and reversed by delactylase, with numerous new enzymes, such as AARS1/2, reported to be involved. Specifically, these studies have revealed how lactylation exerts its influence through alterations in protein spatial conformation, molecular interactions, enzyme activity and subcellular localization. Indeed, lactylation is implicated in various physiological and pathological processes, including tumor development, cardiovascular and cerebrovascular diseases, immune cell activation and psychiatric disorders. This review provides the latest advancements in research on the regulatory roles of non-histone protein lactylation, highlighting its crucial scientific importance for future studies.